Determination of chlorpyrifos in organically grown and conventionally grown vegetables using solid phase extraction (SPE) coupled to gas chromatography electron capture detector (GC-ECD) / Mohamad Azeem Mohd Idris - Mohd Idris, Mohamad Azeem (2017)
Chlorpyrifos in different farming method of vegetables was determined by using solid phase extraction (SPE) and gas chromatography electron capture detector (GC-ECD).SPE sorbent packed with Cis was used in this study. The injector port and detector temperature for GC-ECD analysis were 280 °C and 300 °C respectively with 20.0 mLmin"1 carrier gas flow, while the flow rate for Cis SPE sorbent in extraction of chlorpyrifos was ~ 6 ml per min. The concentration of chlorpyrifos in different samples were determined and compared between home grown, organically grown and conventionally grown. It was found that, the conventionally grown mustard sample(M3) and conventionally grown spinach (S3) have the highest chlorpyrifos concentration, 0.0821 ppm and 0.0922 ppm respectively compared to other vegetable samples.